Correction: Prevalence of Cutaneous Leishmaniasis in Districts of High and Low Endemicity in Mali. - Bourama Traoré; Fabiano Oliveira; Ousmane Faye; Adama Dicko; Cheick A Coulibaly; Ibrahim M Sissoko; Samake Sibiry; Nafomon Sogoba; Moussa Brema Sangare; Yaya I Coulibaly; Pierre Traore; Sekou F Traore; et al. (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0005141.].